2008
DOI: 10.1038/nature07314
|View full text |Cite
|
Sign up to set email alerts
|

In vivo reprogramming of adult pancreatic exocrine cells to β-cells

Abstract: One goal of regenerative medicine is to instructively convert adult cells into other cell types for tissue repair and regeneration. Although isolated examples of adult cell reprogramming are known, there is no general understanding of how to turn one cell type into another in a controlled manner. Here, using a strategy of re-expressing key developmental regulators in vivo, we identify a specific combination of three transcription factors (Ngn3 (also known as Neurog3) Pdx1 and Mafa) that reprograms differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
1,521
3
40

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,882 publications
(1,597 citation statements)
references
References 41 publications
33
1,521
3
40
Order By: Relevance
“…Although it will likely be difficult to apply such methods in humans, we propose that such manipulations will inform as to the mechanisms of plasticity and the epigenomic alterations that need to be induced as facilitatory or directly instructive on cell fate. One landmark in reinvigorating such research comes from the finding that acinar cells could convert into b-cells in vivo when given an adenovirus-borne cocktail of three transcription factors (Ngn3, Pdx1, and MafA) (Zhou et al, 2008) (Fig. 5).…”
Section: Genetic Manipulation-based Reprogrammingmentioning
confidence: 99%
“…Although it will likely be difficult to apply such methods in humans, we propose that such manipulations will inform as to the mechanisms of plasticity and the epigenomic alterations that need to be induced as facilitatory or directly instructive on cell fate. One landmark in reinvigorating such research comes from the finding that acinar cells could convert into b-cells in vivo when given an adenovirus-borne cocktail of three transcription factors (Ngn3, Pdx1, and MafA) (Zhou et al, 2008) (Fig. 5).…”
Section: Genetic Manipulation-based Reprogrammingmentioning
confidence: 99%
“…This is clear in iPS studies, where Oct4, Klf4 and Sox2 are critical to the maintenance of ES cell pluripotency [103], but also applies in other contexts, such as the reprogramming of exocrine cells to β cells in the pancreas, and the progressive reprogramming of B cells into macrophages, and later, into iPS cells [90,91,93]. Pdx1, used in the in vivo pancreas reprogramming and the liver to pancreas cell reprogramming, is critical for pancreas development and islet β cell specification [104,105].…”
Section: Nuclear Reprogrammingmentioning
confidence: 99%
“…Forced transdifferentiation of one cell type into another also requires cellular reprogramming. Most recently, Zhou et al [93] have shown that adult pancreatic exocrine cells can be directly reprogrammed in vivo to insulinsecreting β cells capable of ameliorating hyperglycaemia in a streptozotocin-and fasting-induced mouse model of diabetes. Adult liver cells can also be reprogrammed to take on pancreatic islet β cell characteristics and are also capable of producing insulin and ameliorating hypoglycaemia in diabetic mice [94,95].…”
Section: Nuclear Reprogrammingmentioning
confidence: 99%
“…Nevertheless, de-differentiation in committed cells can be induced by somatic cell nuclear transfer and nonoocyte-based approaches such as fusion of somatic cells with embryonic SCs, treatment of somatic cells with extracts of pluripotent cells, and/or retroviral transduction of somatic cells to overexpress pluripotency genes [2]. Therefore, the capability for reprogramming and transdifferentiation is retained into adulthood [3,4]. The potential for transdifferentiation of differentiated somatic (adult) epithelial SCs opens up novel avenues for regenerative medicine and avoids the ethical issues surrounding the use of embryonic SCs, but it is crucial to ensure the safety of this process [1].…”
Section: Introductionmentioning
confidence: 99%